1990
DOI: 10.1111/j.1365-2958.1990.tb00688.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation at the omp2 porin locus of the brucellae: species‐specific markers

Abstract: The omp2 locus of Brucella abortus is composed of two closely related genes (omp2a and omp2b) that encode, and potentially both express, homologous porin proteins. Genetic variation at this locus is revealed in the form of restriction-fragment-length polymorphisms which can be used to distinguish the type strains of all six Brucella species. Five of the six species contain single copies of omp2a and omp2b, whereas Brucella ovis appears to have two copies of the omp2a gene. The implications of these results wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
0
5

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 14 publications
3
52
0
5
Order By: Relevance
“…The hypothesis of the presence of two similar copies of omp2a in B. ovis, instead of one copy of omp2a and one copy of ompZb for the other Brucella species (Ficht et al, 1990), is supported by our PCR-RFLP results. However, the similarity between the two copies is more divergent in B.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The hypothesis of the presence of two similar copies of omp2a in B. ovis, instead of one copy of omp2a and one copy of ompZb for the other Brucella species (Ficht et al, 1990), is supported by our PCR-RFLP results. However, the similarity between the two copies is more divergent in B.…”
Section: Discussionsupporting
confidence: 76%
“…3). This observation confirms the results published by Ficht et al (1990) concerning the absence of a 120 bp segment in the omp2a genes of B. abortus bv. 1, 2 and 4.…”
Section: Polymorphism Of the Brucella Genes Encoding 36 Kda Ompssupporting
confidence: 82%
See 1 more Smart Citation
“…Recently a molecular biotyping approach has been proposed on the basis of restriction endonuclease polymorphism in the genes encoding the major outer proteins of Brucella membrane [33]. The Omp2 gene exists as a locus of two nearly homologous repeated copies that differ slightly among Brucella species and biotypes [34]. We used previous information to design specific primers that amplify a 720 bp fragment lanes 3, 4 and 5 shows the positive samples taken from first farm after vaccination with RB51 vaccine, whereas lane 7 only positive samples collected from second farms, Lanes 6 and 8 were negative for PCR against brucella species.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of porin gene expression in the other Brucella strains is still unknown. The polymorphism of both porin genes has been extensively studied, and restriction fragment length polymorphism (RFLP) studies have identified 11 omp2b variants and 8 omp2a variants (6,16). The omp2 locus sequences in the different Brucella species show complex variability, involving gene conversion phenomenon between the closely related inverted gene copies (17).…”
mentioning
confidence: 99%